European Elites and Ideas of Empire, 1917-1957 - Gusejnova, Dina (Cambridge University Press, 2016)
A study of the genesis of European civilisation as a concept of 20th-C EU political practice & as a specific project of a transnational network of EU elites, examining how they sought to rehabilitate EU identity as a response to a crisis of belonging following the 1917-1920 revolutions & the collapse of the Hohenzollern, Habsburg & RU Empires.